The effect of YouTube advertisements with skip-button function on young Egyptian women’s purchasing behavior - Donia Adnan Moawad; Hanan Gunied; Asmaa El-Mously (Insights into Language, Culture and Communication, 2023)
This research paper aims at evaluating how entertainment, customization and perceived intrusiveness of the skippable in-stream YouTube advertisement can affect Egyptian millennial women’s attitude towards the skippable in-stream advertisement content, defining the relationship between attitudes towards purchasing and Egyptian millennial women’s intention-to-purchase and determining how intention-to-purchase can affect Egyptian millennial women’s purchasing behavior. An online questionnaire was distributed via different social media platforms: Facebook, WhatsApp and Instagram, with a sample of 392 Egyptian millennial women. It was found that the level of the intrusiveness that Egyptian Millennial women perceive negatively affects their attitude towards the idea of purchasing the product/service presented in the skippable in-stream YouTube advertisement, which in consequence decreases the probability of thinking seriously about buying this product/service or actually buy. On the other hand, it was found that entertainment and customization can lead to a more favorable attitude towards purchasing, which as a result will positively affect the Egyptian millennials women’s intention to purchase and their purchasing behavior positively.  Due to time constraints, some variables were removed, such as: perceived behavioral control and SES (Socio-Economic Status), which resulted in changing Theory of Planned Behavior (TPB) to Theory of Reasoned Action (TRA).   Received: 14 July 2023 Accepted: 05 September 2023 Published: 08 October 2023